ANALISIS PENERAPAN MODEL PEMBELAJARAN PBL, PJBL, DAN DEEP LEARNING PADA PEMBELAJARAN BIOLOGI DI SMA NEGERI 1 PERCUT SEI TUAN - Sitorus , Nurdayanti; Samosir, Newche Rolima; Sinaga, Putri Wanna Oktavia; Samosir, Ayu Triputri; Kudadiri, Wahyuni Sada Arihta; Mukra, Rizal; Arwita, Widya (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2025)
The issue in Biology education at the senior high school level often lies in the lack of active student engagement and the limited development of critical thinking skills fostered through conventional teaching methods. This study aims to analyze the effectiveness of implementing three innovative learning models—Problem-Based Learning (PBL), Project-Based Learning (PJBL), and Deep Learning (DL)—in enhancing the quality of Biology education at SMA Negeri 1 Percut Sei Tuan. The research employed a qualitative descriptive approach through a case study, utilizing questionnaires, observations, and documentation as data collection techniques. The study subjects included eleventh-grade science students and one Biology teacher. The results indicated that students preferred the PJBL model due to its practical and collaborative nature, while the teacher favored the PBL model for its effectiveness in developing critical thinking skills. Meanwhile, the application of DL still faces challenges related to student adaptation and technological readiness. The study recommends integrating PJBL and PBL as complementary approaches to create a more dynamic, interactive, and effective learning environment.